The Relation Between Mother's Knowledge Level, Mother's Attitude and Husband's Support and The Selection of Long-Term Contraception Method (MKJP) in The Working Area of Ulak Karang Public Health Center of Padang - Nega Olavia; Yusrawati; Afriwardi (Institute of Computer Science (IOCS), 2021)
Population growth in Indonesia cannot be avoided. The high rate of population growth in Indonesia is a big problem and it requires attention and handling from all parties, both the community and the government. The government needs to anticipate the problems that occur, including the family planning program. In the National Medium-Term Development Plan (RPJMN), the national family planning program in Indonesia is still directed to the use of the Long-Term Contraceptive Method (MKJP). The purpose of this study was to determine the relation between mother's knowledge level, mother's attitude, and husband's support with the selection of long-term contraceptive method (MKJP) in the working area of the Ulak Karang Public Health Center. This study used a cross sectional design. The population in this study were all active family planning participants in the working area of the Ulak Karang Public Health Center, Padang. The sample in this study was 102 respondents. Data were collected by using questionnaires and data were analyzed by using Chi-Square. From the results of statistical tests, it shows that most of the mothers who use the MKJP contraceptive method have a sufficient level of knowledge of 54 (52.9%), mothers who have a positive attitude of 53 (52.0%), mothers whose husbands support of 54 (52.9 %) who used the MKJP contraceptive method. There is a relation between mother's knowledge level and the selection of a long-term contraceptive method (P=0.005); there is a relation between the mother's attitude and the selection of a long-term contraceptive method (P=0.029); there is a relation between husband's support and the selection of a long-term contraceptive method(MKJP) (p=0,020). The conclusion of this study is that there is a relation between the mother's knowledge level, mother's attitude, and husband's support amd the selection of long-term contraceptive method(MKJP).